Inter‐Organizational Fit, Relationship Management Capability, and Collaborative Performance within a Humanitarian Setting - Moshtari, Mohammad (Production and Operations Management, 2016)
Donors and governments are increasingly calling for more collaborative relationships between humanitarian organizations (HOs), to improve the efficiency and effectiveness of humanitarian operations by exchanging information, knowledge, and resources. This study examines the relative efficacy of partners' characteristics (i.e., compatibility and resource complementarity) and partners' relationship management capability on collaborative relationships, incorporating mutual trust and reciprocal commitment as two mediator constructs. We use Partial Least Squares to examine the proposed hypotheses using a sample of 191 respondents. Data are collected through a web‐survey of international humanitarian non‐governmental organizations (NGOs) in countries across Africa, Asia, and South America. The results reveal that (i) resource complementarity and relationship management capability are significant factors influencing collaborative performance through their effects on partners' mutual trust and reciprocal commitment, and that (ii) partners' compatibility (i.e., missions, values, and operational methods) does not significantly drive success or failure of collaboration between international NGOs. These results suggest that given the present diversity of HOs' characteristics, the success of collaboration is associated with the partners' level of understanding of each other's objectives, operations, and values, and to the extent to which organizations efficiently communicate and coordinate their joint activities. The managerial implications of the findings are also discussed.